Optical Sensor Fabricated From Beta Gallium Oxide Nanorods - Mai-Dinh , My-Duyen; Duong , Minh-Dat; Nguyen, Khanh; Nguyen, Tien-Luat; Nguyen, Ngoc-Hung; Do, Huy-Binh (Journal of Technical Education Science, 2025)
Beta gallium oxide (β-Ga2O3) has attracted lots of attentions for the applications in optical devices. 1-D and 2-D β-Ga2O3 can be synthesized by several simple methods such as hydrolysis, sol-gel, electrospinning, and hydrothermal methods. In this study, β-Ga2O3 nanorods were prepared via the hydrothermal method. The morphology and crystal structure of β-Ga2O3 nanorods were investigated using FESEM image, and XRD patterns, respectively, confirming that Ga2O3 has monoclinic structure. FTIR spectrum was utilized to find the representative vibration bands in β-Ga2O3 nanorods, illustrating the Ga-O-Ga bending vibration and Ga-O stretching vibration at 670 cm-1 and 450 cm-1, respectively. The optical sensor was successfully fabricated based on β-Ga2O3 nanorods powder and graphene oxide powder which served as the medium for charges transport. The sensor was excited with the wavelength of 405 nm and the excitation power of 45mW/cm2. It was found that the β-Ga2O3 nanorods optical sensor had the rise time and fall time of 1.6 s, and the responsivity of 1.48×10−4 A/W, providing the applicability of this type of devices. The study shows a solution to fabricate an optical sensor from β-Ga2O3 nanorods.